"Embedded regulation:" The migration of objects, scripts, and governance. Issue 3 (10th October 2012) - Cloatre, Emilie; Dingwall, Robert
Abstract This paper asks why an officially unregulated market in pharmaceuticals in a least developed country, Djibouti, behaves as if it were strictly regulated, with limited access to a small number of high‐cost drugs. We use Actor‐Network Theory (ANT) to show that the explanation is more complex than critics of the international pharmaceutical industry have supposed. Regulation and property rights generated in developed countries have become embedded in the drugs and "black boxed" to the point of invisibility. This has allowed them to travel to Djibouti with the drugs, while maintaining their effects in action. This case study develops our understanding of the way in which materials that are not designated as regulatory agents may still have regulatory impacts through their ability to enrol complex networks of actors, rules, values, and practices. Finally, it argues against the notion of law as a fixed and distinctive space for action, as opposed to the ANT vision of a fluid and contingent order, where law is part of a socio‐technico‐legal alliance that happens to achieve certain effects.